Implementasi Smart Home Berbasis IoT: Studi Simulasi Menggunakan Cisco Packet Tracer - Ondihon Parlinggoman Munthe; Alz Danny Wowor (LKP Unity Academy, 2025)
The rapid development of Internet of Things (IoT) technology enables automatic and remote control of home appliances. However, direct hardware implementation often entails high costs and complex configurations. This study aims to design and analyze the performance of a Smart Home system through a simulation approach using Cisco Packet Tracer software. The method encompasses network topology design, core network service configuration, and functionality and Quality of Service (QoS) testing to validate the proposed design. Simulation results demonstrate that the constructed system operates successfully, with the Smartphone effectively controlling electronic devices in real-time. QoS testing recorded 0% packet loss and an average latency of 27 ms, indicating reliable connectivity between user devices and the IoT Server. This study concludes that simulation using Cisco Packet Tracer is effective as a preliminary validation stage in designing Smart Home infrastructure before physical implementation.